2015
DOI: 10.1074/jbc.m115.657874
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Antibody Recognition of Lipid A

Abstract: Background: Lipid A-specific antibodies are not effective in sepsis treatment; infection by Gram-negative bacteria can induce autoimmune disease. Results: Antibody-combining sites orient lipid A to bury the LPS attachment point and can cross-react with ssDNA through terminal nucleotides. Conclusion: Anti-lipid A antibodies cannot bind full-length LPS; phosphates play a crucial role in polyspecificity. Significance: Antibody recognition of lipid A illuminates the genesis of autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
6
0
1
Order By: Relevance
“…It has been shown that anti-lipid A antibodies may cross-react with the lipid A of different species of bacteria, as well as with molecules present in humans, such as ssDNA, cardiolipin, or ligands on human B lymphocytes. It is believed that the cross-reactivity between lipid A and other host molecules may affect the development of autoimmune diseases [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that anti-lipid A antibodies may cross-react with the lipid A of different species of bacteria, as well as with molecules present in humans, such as ssDNA, cardiolipin, or ligands on human B lymphocytes. It is believed that the cross-reactivity between lipid A and other host molecules may affect the development of autoimmune diseases [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the presence of the V H 10 CDR2 loop seems to be critical for DNA binding in this experimental setup, corroborating the role for the CDR2 in V H 10 germline sequences. The importance of heavy chain CDR2 in antigen binding has been reported before [25,30].…”
Section: Discussionmentioning
confidence: 95%
“…All models showed a single-chain conventional VH-VL pairing. Compared to another pre-BCR structure in PDB (2H32), it showed a Sequence alignment of the V H 10 chain used in scpre-BCR with the two anti-DNA antibodies 1CBV [24], 4Z8F [25] shows that the V chain sequences are very similar and share the adjacent arginine residue at position 50 and 52 (Figure 6). Thus, a potential salt-bridge could be formed with DNA's phosphate groups, allowing the V H 10 germline chain the ability to bind DNA independently of CDR3 or the V L domain.…”
Section: A Structural Model Of Scprebcr-vh10 Supports Dna Intrinsic Binding For Dnamentioning
confidence: 99%
“…Более того, на основе моноклональных антител к липиду А разработана иммунохимическая тест-система, позволяющая с удовлетворительной чувствительностью (10 5 клеток/ мл) выявлять бактерии Escherichia coli O157 [69]. Вместе с тем многочисленные исследования, направленные на разработку терапевтических средств на основе моноклональных антител к липиду А ряда грамотрицательных бактерий, к настоящему времени не завершились успешными клиническими испытаниями [26]. Будущие исследования должны показать, способны ли сами клетки патогенных иерсиний, а не только выделенный из них препарат ЛПС, связываться с эукариотической клеткой посредством липида А.…”
Section: небелковые адгезиныunclassified